اسلوب مقترح لتنضيم محتوى الكتب المدرسية - أ.د.عـلي مطني عـلي العنبكي; م.م.سھام عبد غـیدان المھداوي (مجلة الفتح للبحوث التربوية والنفسية, 2023)
الملخص ھناك الكثیر من الصعوبات تواجھ المتعلمین في إكتساب المفاھیم.فاشارت الكثیر من الدراسات الى أن ھناك عدد من الاخطاء في إكتساب المفاھیم.وعزت ذلك الى أسباب كثیرة.إلا ّ أن الباحثین یریان أن سبب ذلك قد یعود الى عدم إستخدام إسلوب التنظیم الھرمي للمفاھیم في بناء محتوى الكتب المدرسیة. وتھدف الدراسة الحالیة الى وضع الاساس النظري لتنظیم محتوى الكتب المدرسیة بالاسلوب الھرمي للمفاھیم،وشرح ھذا الاسلوب بالامثلة.كي یسھل على لجان تالیف الكتب المدرسیة فھمھ،وبالتالي إمكانیة إستخدامھ في عملیة تالیفھا. A suggested style for organizing contents of textbooks By Prof.Dr.Ali Matni Ali AL Anbiky assist. teacher.SihamAbdGhaidan Basic Education College / Diyala University Abstract There are a great difficulties, face the learners in acquisition concepts, many studies comes out, that many mistakes are done because of many factors. But the researchers thought that the reason of these mistakes due to non using of the Hierarchical organization of the concepts in building the contents of textbooks. The aim of this study is to put the theoretical background for organizing contents of textbooks, by Hierarchical style of concepts, and explain this style to be considered from textbooks authors, and used it in future.